Altman’s Z”-Scores for financial distress predictions among food and beverages industry in Indonesia - Ruth Samantha Hamzah; Mutiara Lusiana Annisa (Owner : Riset dan Jurnal Akuntansi, 2022)
The food and beverage industry is an accelerated sector in Indonesia. They are predicted to be one of the pivotal sectors supporting manufacturing and economic growth. This study aims to predict financial distress on food and beverage industries in Indonesia using Altman's Z”-Score modification model. The samples of this study are 48 firm-year observations in the period of 2018 and 2019. The results show there are 2.1 percent of firms experienced financial distress (Z < 1.10), 2.1 percent of firms was in grey area, i.e., prone to financial distress (Z < 1.10 < 2.60), and 95.8 percent of firms did not experience financial distress. It implies that food and beverage industries in Indonesia is relatively safe if there is no economic shock. Furthermore, the prediction is able to be considered either for stakeholders or shareholders in decision making and financial policies, respectively. Nevertheless, the signal is given for firms that are included in financial distress and grey area.